Screening for Novel LOX and SOD1 Variants in Keratoconus Patients from Brazil - Diego Nery Benevides Gadelha; Alex Felipe Barbosa Feitosa; Rafaela Gomes da Silva; Luana Talita Antunes; Matheus Cavalcanti Muniz; Matheus Alencar de Oliveira; Dáfine de Oliveira Andrade; Nathalia Mayanna da Paz Silva; Sebastião Cronemberger; Bruno Luiz Fonseca Schamber-Reis (Journal of Ophthalmic & Vision Research, 2020)
Purpose: To investigate the presence of the variants of lysyl oxygenase (LOX) and superoxide dismutase 1 (SOD1) genes in Brazilian patients with advanced keratoconus. Methods: Donor genomic DNA extracted from blood samples was screened for 5'UTR, exonic LOX, and SOD1 variants in a subset of 26 patients presenting with advanced keratoconus (KISA